The biosensor toolbox for plant developmental biology - Uslu, Veli Vural; Großmann, Guido (Current opinion in plant biology, 2016)
Plant development is highly interconnected with the metabolic state of tissues and cells. Current research efforts focus on the identification of the links and mechanisms that govern the interplay between metabolic and gene-regulatory networks. Genetically encoded sensors that allow detection of small molecules in vivo and at high spatio-temporal resolution promise to be the tools of choice for quantifying and visualizing the dynamics of metabolite flux in plants. We provide an overview about current approaches to measure signaling molecules, such as hormones, calcium and sugars, as well as for monitoring the metabolic state via energy equivalents and pH. Biosensors show great potential to address questions of plant development but there are also limitations where alternative approaches are needed.
Gesehen am 29.05.2020